Cyclodextrins: from solute to solvent. Issue 23 (26th February 2020) - El Achkar, Tracy; Moufawad, Tarek; Ruellan, Steven; Landy, David; Greige-Gerges, Hélène; Fourmentin, Sophie
Abstract : A new deep eutectic solvent (DES), based on a methylated-β-cyclodextrin and levulinic acid, exhibiting supramolecular properties is presented here for the first time. Abstract : A supramolecular solvent based on cyclodextrin (CD) is presented here for the first time. Indeed, a low melting mixture was obtained by mixing levulinic acid and a CD derivative, which retained its inclusion ability in the resulting solvent. This new system gives rise to a new family of solvents that could be called SUPRADES (supramolecular deep eutectic solvents).